Comparison of the Simple Additive Weighting (SAW) with the Technique for Others Reference by Similarity to Ideal Solution (TOPSIS) methods - Tahyudin, Imam; Rosyidi, Rahman; Saleh Ahmar, Ansari; ., Haviluddin (International Journal of Engineering and Technology, 2018)
The purpose of this research is to compare the SAW and TOPSIS methods. This research uses data selection of education scholarship in an Indonesian public school. This research uses data from selection of education scholarship program in an Indonesian public school. The methods usage is SAW and TOPSIS methods. A comparison of the two methods using this data set demonstrates that SAW method was more accurate than TOPSIS method.
Keywords: SAW; TOPSIS; Scholarship selection.